(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
The speed at which the demand for energy is increasing around the world has led to anxiety over supply insufficiency. The difficulties associated with setting up energy infrastructure is an additional concern. This paper reviews the amount of energy required by structures and identifies different variables that influence the use of energy by buildings. The energy requirement of a teaching hospital in Iraq was determined (i.e. its energy performance was determined). The energy performance of a building is related to its Building Energy Index (BEI). BEI is measured in kWh/m2/yr and is an indication of how efficient a building is with respect to its usage of energy, i.e. the value of the BEI of buildings helps to ascertain which building is more efficient than the other in their usage of energy.The results of this review indicate that the load and time usage factors are directly proportional to the BEI. The hospital’s BEI was determined to be 235 and this value was compared with those of other studies.